2022
DOI: 10.3390/molecules27154768
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Evaluation of the Antimicrobial Activity of Thymol—Major Compounds in the Essential Oil of Lippia thymoides Mart. & Schauer (Verbenaceae)

Abstract: In this paper, we evaluated the drug-receptor interactions responsible for the antimicrobial activity of thymol, the major compound present in the essential oil (EO) of Lippia thymoides (L. thymoides) Mart. & Schauer (Verbenaceae). It was previously reported that this EO exhibits antimicrobial activity against Candida albicans (C. albicans), Staphylococcus aureus (S. aureus), and Escherichia coli (E. coli). Therefore, we used molecular docking, molecular dynamics simulations, and free energy calculations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The MolDock Score (GRID) function was used with a grid resolution of 0.30 Å and a radius of 5 Å encompassing the entire connection cavity. A description of the method can be found in [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…The MolDock Score (GRID) function was used with a grid resolution of 0.30 Å and a radius of 5 Å encompassing the entire connection cavity. A description of the method can be found in [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…[57] Another research paper demonstrated that the fungicidal effect of thymol and carvacrol could be explained by the presence of hydroxyl group on the phenolic ring that provides hydrophilic ability to both compounds, facilitating their dissolution in the microbial membrane and leading to ergosterol biosynthesis impairment. [58] Moreover, recent study conducted by Cruz et al [59] stipulated that thymol, as a major compound in Lippia thymoides (EO), exhibited antimicrobial activity against (C. albicans) by targeting the CYP51. Furthermore, a study performed by Bishoyi et al [60] showed that a thymol derivate congener (4-((4-hydroxy-5-isopropyl-2-methylbenzyl)amino)-N- (5-methylisoxazol-3-yl) benzene sulfonamide had a high docking score at (À 9.5) kcal/mol against the fungal target (CYP51).…”
Section: In Silico Evaluation Of Carvacrol and Thymol Antifungal Prop...mentioning
confidence: 99%
“…Thymol (2-isopropyl-5-methylphenol) is the main monoterpene phenol occurring in essential oils isolated from plants belonging to the Lamiaceae family (Thymus, Ocimum, Origanum, and Monarda genera) and other plants such as those belonging to the Verbenaceae, Scrophulariaceae, Ranuncolaceae, and Apiaceae families [8]. Because of its high safety, wide range of sources, lack of chemical residues, broad-spectrum antifungal properties, and other characteristics [9,10], it has been authorized by the Federal Drug Administration (FDA) for food and as a food additive, and it has since been widely utilized in the field of food preservation [11]. Thymol has been demonstrated to be capable of being transformed into microencapsulation [12] and antimicrobial films [13] in order to effectively extend the freshness period of fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%